2020
DOI: 10.2166/wst.2020.540
|View full text |Cite
|
Sign up to set email alerts
|

Sewage surveillance for the presence of SARS-CoV-2 genome as a useful wastewater based epidemiology (WBE) tracking tool in India

Abstract: The infection with SARS-CoV-2 is reported to be accompanied by the shedding of the virus in faecal samples of infected patients. Earlier reports have suggested that COVID-19 agents can be present in the sewage samples and thus it can be a good indication of the pandemic extent in a community. However, no such studies have been reported in the Indian context. Hence, it becomes absolutely necessary to detect the presence of the SARS-CoV-2 in the wastewater samples from wastewater treatment plants (WWTPs) serving… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(109 citation statements)
references
References 26 publications
4
104
0
1
Order By: Relevance
“…Additionally, the identification methods of aqueous as well as solid-phase SARS–CoV–2 should be taken into consideration during quantification of SARS–CoV–2 gene concentrations and loads shed in wastewater and accordingly, meticulous periodic protocols should be developed for measuring clean-up and RT–qPCR ( Weidhaas et al, 2021 ). Currently, multiple studies have recorded the detection of SARS–CoV–2 RNA in wastewater ( Ahmed et al, 2020b ; Kocamemi et al, 2020 ; Arora et al, 2020 ; Balboa et al, 2020; Bar Or et al, 2020 ; Chavarria-Miró et al, 2020 ; Collivignarelli et al, 2020 ; Green et al, 2020 ; Haramoto et al, 2020 ; Han et al, 2020 ; Kumar et al, 2020b ; La Rosa et al, 2020b ; Medema et al, 2020 ; Nemudryi et al, 2020 ; Peccia et al, 2020 ; Randazzo et al, 2020a , 2020b ; Rimoldi et al, 2020 ; Sharif et al, 2020 ; Wu et al, 2020b ; Wurtzer et al, 2020 ). The summary of the prevalence of SARS-CoV-2 RNA in the category of wastewater samples, the viral concentration and the detection technique engaged in each continent and country are represented in Table 1 .…”
Section: Sars-cov-2 Rna Detection Methods In Wastewater and Wastewater-based Epidemiology (Wbe)mentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the identification methods of aqueous as well as solid-phase SARS–CoV–2 should be taken into consideration during quantification of SARS–CoV–2 gene concentrations and loads shed in wastewater and accordingly, meticulous periodic protocols should be developed for measuring clean-up and RT–qPCR ( Weidhaas et al, 2021 ). Currently, multiple studies have recorded the detection of SARS–CoV–2 RNA in wastewater ( Ahmed et al, 2020b ; Kocamemi et al, 2020 ; Arora et al, 2020 ; Balboa et al, 2020; Bar Or et al, 2020 ; Chavarria-Miró et al, 2020 ; Collivignarelli et al, 2020 ; Green et al, 2020 ; Haramoto et al, 2020 ; Han et al, 2020 ; Kumar et al, 2020b ; La Rosa et al, 2020b ; Medema et al, 2020 ; Nemudryi et al, 2020 ; Peccia et al, 2020 ; Randazzo et al, 2020a , 2020b ; Rimoldi et al, 2020 ; Sharif et al, 2020 ; Wu et al, 2020b ; Wurtzer et al, 2020 ). The summary of the prevalence of SARS-CoV-2 RNA in the category of wastewater samples, the viral concentration and the detection technique engaged in each continent and country are represented in Table 1 .…”
Section: Sars-cov-2 Rna Detection Methods In Wastewater and Wastewater-based Epidemiology (Wbe)mentioning
confidence: 99%
“…Coincidentally, in a study performed in the US, 100% of wastewater samples that had been treated through the secondary stage treatment of ASP reflected the negative presence of SARS-CoV-2 RNA. On the contrary, a study by Arora et al (2020) revealed the presence of SARS-CoV-2 RNA in the samples that were treated through SBR, AS and MBBR wastewater treatment processes. Notably, considering the COVID-19 pandemic, SBR and MBBR have been proved to be efficient secondary treatment techniques for removing SARS-CoV-2 RNA from the wastewater, according to the latest research of Balboa et al (2021) .…”
Section: Approaches To Processes For the Removal Of Sars-cov-2 In Wastewater Processing Plantsmentioning
confidence: 96%
See 1 more Smart Citation
“… Effluent from WWTP1: 25 May: 20 GU/mL 15 Jun: 167 GU/mL Effluent from WWTP2: 25 May: 10 GU/mL Arora et al. 33 Jaipur, Rajasthan, India. From May 3 to June 14, 2020.…”
Section: Reduction Of Sars-cov-2 In Wastewater Treatment Plantsmentioning
confidence: 99%
“… 26 Some studies have tested hospital wastewater influents and effluents to determine if the chlorine-based disinfection methods are sufficient. Although Wang et al and Arora et al have reported only negative hospital wastewater effluent samples for SARS-CoV-2, 24 , 27 Zhang et al reported that even though influents from the Wuchang Cabin Hospital were negative, effluent samples were positive for the virus. This suggests that chlorine disinfection was enough to destroy the virus in the aqueous phase of the influent; however, the viruses embedded in the stool particles were less affected.…”
Section: Effect Of Wastewater Treatment On Sars-cov-2 Survivability and Potential Transmission Of Sars-cov-2 Through Wastewatermentioning
confidence: 99%